Pengaruh Model Pembelajaran Generatif Terhadap Kemampuan Pemecahan Masalah Matematika - Arif Rahman Hakim (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2014)
The aim of this research is to obtain empirical data on the influence of using learning generative model towards problem solving outcomes. This research used the experiment method at SMA Negeri 1 Dukupuntang, Kabupaten Cirebon. In this research was done by taking two classes; experiment class and control class, experiment class consists of 39 students and control class consists of 40 students. The instrument that is used in this research is test with using essay questions which have been validated empirically. Data analysis used in this research is ???? test. The result of this research is there is significant influence between using of learning generative model towards problem solving outcomes at SMA Negeri 1 Dukupuntang, Kabupaten Cirebon.